Glucose metabolism in systemic juvenile idiopathic arthritis - Papatsorn Suppasit; Soamarat Vilaiyuk; Preamrudee Poomthavorn; Sarunyu Pongratanakul; Patcharin Khlairit; Pat Mahachoklertwattana (BMC, 2022)
Abstract Background Systemic juvenile idiopathic arthritis (SJIA) is a chronic systemic inflammatory disease in children. Overproduction of inflammatory cytokines in SJIA resembles that in adult onset Still disease. Chronic inflammation causes insulin resistance and consequently leading to abnormal glucose metabolism. Adults with rheumatoid arthritis (RA) have increased risks of abnormal glucose metabolism and diabetes. To date, glucose metabolism in patients with SJIA has not been elucidated. Methods Patients with SJIA aged 4-25 years were recruited. All patients underwent an oral glucose tolerance test (OGTT). Indices of insulin sensitivity [homeostasis model assessment for insulin resistance (HOMA-IR) and whole-body insulin sensitivity index (WBISI)] and β-cell function [insulinogenic index (IGI) and disposition index (DI)] were calculated. Obese children with normoglycemia who underwent the OGTT were served as a control group. Results A total of 39 patients with SJIA, aged 4-25 years, median (IQR) BMI SDS was 0.1 (-0.5 to 1.7). Patients were divided into 2 groups, overweight/obese (OW/OB) (n = 11) and lean (n = 28). Only one obese patient had prediabetes and none had diabetes. In comparison with sex- and age-matched OW/OB controls (n = 33), OW/OB patients with SJIA had higher insulin resistance [median (IQR) HOMA-IR: 2.6 (2.1-3.3) vs 1.5 (0.8-2.0), p = 0.001], lower insulin sensitivity [median (IQR) WBISI: 3.7 (2.7-5.9) vs 5.4 (4.5-8.7), p = 0.024], and higher insulin secretion [median (IQR) IGI: 2.5 (2.0-3.5) vs 1.0 (0.8-1.9), p = 0.001]. In lean patients with SJIA, insulin sensitivity indices seemed to be comparable with those of lean controls. Conclusions Overweight/obese children with SJIA seemed to have increased insulin resistance and thus may have an increased risk for developing diabetes.